Effect of Motivation on Employee Performance of Commercial Banks in Tilottama Municipality - Baral, Anil; Lamsal, Rajendra (NPRC Journal of Multidisciplinary Research, 2025)
Motivating factors play an important role in enhancing employee performance. Various studies have examined the effect of motivation on employee performance; however, very few have been conducted in Nepal at the financial institutional level, such as commercial banks. Similarly, the effects of various motivational factors in commercial banks have not been studied much in Nepal. Thus, this study examined the effect of various factors of motivation, especially monetary reward, promotion, recognition and working environment, on employee performance in commercial banks of Tilottama Municipality, Rupandehi, Nepal. Forty branches of 15 commercial banks (262 employees) operating in the municipality were selected, and questionnaires were distributed to all 262 employees; however, only 235 valid responses were obtained. Various analytical methods, including descriptive statistics, reliability tests, correlation and regression analyses, and ANOVA, were used to test relationships among the dependent and independent variables. It was found that employees agreed with statements about receiving a good monetary reward, a good working environment, being satisfied with their promotion, and being recognised for their contributions. The working environment showed a stronger positive relationship with employee performance than monetary rewards and promotion. However, the effect of recognition was found to be statistically insignificant in the regression model. Thus, the working environment, monetary rewards, and promotion are considered the best ways to enhance employee performance. This study can help commercial banks, other financial institutions, and policymakers strengthen institutional productivity and profitability by improving employee performance.